Characteristics of biofilm formation process in the bioelectrochemical systems, working in batch-mode of cultivation - Zubchenko, Liudmyla; Kuzminskiy, Yevhen (Lviv Politechnic Publishing House, 2017)
У статті приведено короткий огляд методу формування анодної біоплівки з високою екзоелектро- генною активністю, який включає почергові повну і часткову заміну поживного середовища. Проаналізовано вплив процесу адаптації на генерування електричного струму під час фор- мування біоплівки. Пояснено причини різкого варіювання сили струму відразу після заміни поживного середовища..

A short overview of the formation methods of the biofilm with high exoelectrogens activity, which includes alternate partial and complete changes of culture medium, was done in the article. The influence of adaptation processes on electric current generation during the exoelectrogens biofilm formation was analyzed. The article also describes the reasons of sharp current variation, which appeared after nutrient medium changes.
Параметри процесу формування біоплівки в біоелектрохімічних системах при періодичному режимі культивування
Keywords: мікробні паливні елементи; екзо- електрогени; анодна біоплівка; очищення стічних вод; microbial fuel cells; exoelectrogenes; anodic biofilm; wastewater treatment